A Systematic Review of Contaminants of Concern in Uganda: Occurrence, Sources, Potential Risks, and Removal Strategies - Baguma, Gabson; Bamanya, Gadson; Gonzaga, Allan; Ampaire, Wycliffe; Onen, Patrick (https://doi.org/10.3390/ pollutants3040037, 2023)
Contaminants of concern (CoCs) pose significant threats to Uganda’s ecosystems and public health, particularly in the face of rapid urbanization, industrial expansion, and intensified agriculture. This systematic review comprehensively analyzed Uganda’s CoC landscape, addressing imminent challenges that endanger the country’s ecosystems and public health. CoCs, originating from urban, industrial, and agricultural activities, encompass a wide range of substances, including pharmaceuticals, personal care products, pesticides, industrial chemicals, heavy metals, radionuclides, biotoxins, disinfection byproducts, hydrocarbons, and microplastics. This review identified the major drivers of CoC dispersion, particularly wastewater and improper waste disposal practices. From an initial pool of 887 articles collected from reputable databases such as PubMed, African Journal Online (AJOL), Web of Science, Science Direct, and Google Scholar, 177 pertinent studies were extracted. The literature review pointed to the presence of 57 pharmaceutical residues and personal care products, along with 38 pesticide residues and 12 heavy metals, across various environmental matrices, such as wastewater, groundwater, seawater, rainwater, surface water, drinking water, and pharmaceutical effluents. CoC concentrations displayed significant levels exceeding established regulations, varying based on the specific locations, compounds, and matrices. This review underscores potential ecological and health consequences associated with CoCs, including antibiotic resistance, endocrine disruption, and carcinogenicity. Inefficiencies in traditional wastewater treatment methods, coupled with inadequate sanitation practices in certain areas, exacerbate the contamination of Uganda’s aquatic environments, intensifying environmental and health concerns. To address these challenges, advanced oxidation processes (AOPs) emerge as promising and efficient alternatives for CoC degradation and the prevention of environmental pollution. Notably, no prior studies have explored the management and mitigation of these contaminants through AOP application within various aqueous matrices in Uganda. This review emphasizes the necessity of specific regulations, improved data collection, and public awareness campaigns, offering recommendations for advanced wastewater treatment implementation, the adoption of sustainable agricultural practices, and the enforcement of source control measures. Furthermore, it highlights the significance of further research to bridge knowledge gaps and devise effective policies and interventions. Ultimately, this comprehensive analysis equips readers, policymakers, and regulators with vital knowledge for informed decision-making, policy development, and the protection of public health and the environment.